Tax education and fear-appealing messages: A grease or sand in the wheels of tax compliance? - Alhassan Yusif Trawule; Samuel Gameli Gadzo; Holy Kwabla Kportorgbi; Richmond Sam-Quarm (Cogent Business & Management, 2022)
The phenomenon of tax education, fear-appealing, and the convenience of tax has become vital in contemporary tax revenue discourse as it is believed that non-compliance of tax has adverse implications on the revenue generation capacity, especially in developing countries. This study departs from the traditional studies on tax compliance by examining the relationship between tax education, committed tax compliance, and capitulative tax compliance among the self-employed in the context of a hierarchical regression. The research design was cross-sectional and correlational using a sample of 400 respondents from a population of 28,355. The results show that albeit tax education and the convenience of tax compliance act as grease in the wheels of committed tax compliance, with both establishing a significant positive relationship with committed tax compliance while fear-appealing messages act as sand in the wheels of committed tax compliance. Also, convenience tax compliance positively influences committed tax compliance while general tax knowledge, fear-appealing messages, and convenience compliance have a unique contribution to capitulative tax compliance. Based on these findings, it is recommended that the revenue authorities should make tax laws less complex to reduce the cost of compliance and enhance tax convenience. Also, regulators of the education sector in conjunction with the revenue authorities should introduce basic tax education as a compulsory course into the school curriculum to boost general tax knowledge because it enhances tax compliance.
Keywords: 650; capitulative tax compliance hierarchical regression; committed tax compliance; Tax education